Exploration of difficulty accessing the mouths of intubated and mechanically ventilated adults for oral care: A video and photographic elicitation study. Issue 11 (20th August 2019) - Dale, Craig M.; Angus, Jan E.; Sutherland, Susan; Dev, Shelly; Rose, Louise
Abstract: Aim: To explore descriptors of difficulty accessing the mouths of intubated and mechanically ventilated adults for oral care, consequences, modifiable antecedents and recommendations for improving care delivery. Background: Nurses report oral access and care delivery difficulty in most mechanically ventilated patients. Design: A prospective qualitative descriptive design. Methods: Data were collected using video and photographic elicitation interviews focused on delivery of oral care. Directed content analysis was used to explore descriptive categories. Reporting used the SRQR guidelines. Setting and participants: A university‐affiliated hospital in Toronto, Canada. Participants included clinicians experienced in accessing the oral space of adults representing nursing, medicine, dentistry and allied health professionals. Findings: We recruited 18 participants; 9 representing critical care and 9 other specialties frequently accessing the mouth, that is dentistry. Descriptors for observed difficulty accessing the oral cavity were "oral crowding with tubes" and "aversive patient responses", which were considered to result in insufficient oral care. Participants perceived aversive patient responses (e.g. biting, turning head side to side, gagging, coughing) as a consequence of forced introduction of instruments inside a crowded mouth. A key finding identified by participants was the observation of substantial procedural pain during oral care interventions. Potentially modifiable antecedents to difficult oral care delivery identified were procedural pain, oral health deterioration (e.g. xerostomia) and lack of interprofessional team problem‐solving. Recommendations to address these antecedents included patient preparation for oral care through verbal and nonverbal cueing, pharmacological and nonpharmacological strategies, and ICU interprofessional education. Conclusions: Oral care in mechanically ventilated adults is complex and painful. Visual research methods offer important advantages for oral care exploration including its ability to reveal less visible aspects of the nurse–patient encounter, thereby enabling novel insights and care. Relevance for clinical practice: Interprofessional education and training in oral health and care interventions tailored to mechanically ventilated patients are recommended.